ANALISIS KESALAHAN ARTIKULASI BAHASA INDONESIA SISWA SEKOLAH DASAR DI WAMENA: PERBANDINGAN DUA SEKOLAH DAN IMPLIKASI PEMBELAJARAN FONETIK KONTEKSTUAL - Robert Jumaikel Nusalawo; Yogi Marulitua Ambarita; Gerson Manuel; Elisabet Ida Suparyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes patterns of Indonesian articulation errors among elementary school students in Wamena and compares findings across two schools to formulate context-specific pedagogical recommendations. Using a descriptive approach based on observational data of target-word articulations, errors were classified into substitution, distortion, elision, and epenthesis, guided by a contextual phonological framework and stakeholder interviews as the methodological design and rationale. Results from 70 students (40 from SD Lachairoi Hom-Hom; 30 from SD YPPGI Napua) show mean articulation errors per student of 3.3 (Lachairoi) and 3.1 (Napua). The most frequent patterns at both schools were /r/→/l/ substitution (9 cases at Lachairoi; 7 at Napua), /s/ distortion (five cases at each school), /k/ substitution (predominantly /k/→/g/ or /k/→/t/ at Lachairoi; notably /k/→/t/ at YPPGI Napua), elision of final –n (more frequent at Lachairoi), and epenthesis (present at both sites). The findings indicate that local first-language phonological interference strongly contributes to variation in Indonesian articulation. Accordingly, phonetic instruction grounded in local cultural knowledge and stepwise articulatory training targeting critical contrasts (/r/–/l/, /k/–/g/–/t/, fricative /s/) is recommended.